2014
DOI: 10.1371/journal.pone.0086426
|View full text |Cite
|
Sign up to set email alerts
|

Increased Metabolite Levels of Glycolysis and Pentose Phosphate Pathway in Rabbit Atherosclerotic Arteries and Hypoxic Macrophage

Abstract: AimsInflammation and possibly hypoxia largely affect glucose utilization in atherosclerotic arteries, which could alter many metabolic systems. However, metabolic changes in atherosclerotic plaques remain unknown. The present study aims to identify changes in metabolic systems relative to glucose uptake and hypoxia in rabbit atherosclerotic arteries and cultured macrophages.MethodsMacrophage-rich or smooth muscle cell (SMC)-rich neointima was created by balloon injury in the iliac-femoral arteries of rabbits f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 36 publications
6
46
1
1
Order By: Relevance
“…Mass spectrometry‐based metabolomics analyses performed in rabbit arteries demonstrated that the levels of numerous metabolites derived from bioenergetic pathways are increased in arteries containing macrophage‐rich neointima, compared with uninjured arteries or smooth muscle cell‐rich neointima . In particular, metabolites from glycolysis and the PPP were markedly increased as well as citrate, fumarate and succinate, similar to what is observed in activated macrophages .…”
Section: Modulation Of Macrophage Metabolism In Atherosclerosissupporting
confidence: 56%
See 1 more Smart Citation
“…Mass spectrometry‐based metabolomics analyses performed in rabbit arteries demonstrated that the levels of numerous metabolites derived from bioenergetic pathways are increased in arteries containing macrophage‐rich neointima, compared with uninjured arteries or smooth muscle cell‐rich neointima . In particular, metabolites from glycolysis and the PPP were markedly increased as well as citrate, fumarate and succinate, similar to what is observed in activated macrophages .…”
Section: Modulation Of Macrophage Metabolism In Atherosclerosissupporting
confidence: 56%
“…Increased metabolites from the PPP were found in rabbit atherosclerotic arteries . The few studies that focus on the role of the PPP in atherosclerosis point out a detrimental role for the PPP in lesion formation.…”
Section: Modulation Of Macrophage Metabolism In Atherosclerosismentioning
confidence: 98%
“…Sarrazy et al () find that glucose uptake and aerobic glycolysis significantly increase in atheromatous plaques of ApoE −/− mice. Yamashita et al () also reveal that metabolite levels of aerobic glycolysis increases in rabbit atherosclerotic arteries. Thus, Warburg effect is found in atherosclerosis process.…”
Section: The Role Of Warburg Effect In Heart Diseasesmentioning
confidence: 91%
“…Derlin et al [15] examined the topographic relationship between arterial 11 C-acetate uptake and vascular calcification in oncology patients, and indicated that 11 C-acetate uptake may represent the early stages of disease. Although there have been few studies on the use of 11 C-acetate for the imaging of atherosclerotic plaques, in our recent metabolome study in a rabbit model, markedly increased acetyl-CoA levels were found in macrophage-rich lesions [35]. Further studies, including comparative studies with …”
Section: Pet/spect Probes For Imaging Targets Other Than Inflammatorymentioning
confidence: 82%
“…On the other hand, it is reported that glucose metabolism and 18 F-FDG uptake in macrophages are more strongly enhanced by hypoxic stimuli than by pro-inflammatory cytokines. Indeed, 18 F-FDG uptake was positively associated with hypoxic areas in atherosclerotic arteries induced by balloon injury in rabbits fed with a high-cholesterol diet [35]. However, high 18 F-FDG uptake was also observed in nonhypoxic macrophage-rich regions of the arteries.…”
Section: Pet/spect Probes For Imaging Inflammatory Cellsmentioning
confidence: 94%